145 Mind the App: A Guide for the Orthopaedic Senior House Officer on Call. (12th October 2021) - Patel, B; Fennelly, J; Frazer, S; Ahmed, M; Granville-Chapman, J
Abstract: Aim: Many senior house officers (SHOs) have little experience in Trauma and Orthopaedics. While junior doctors are encouraged to seek help from the registrar during on call shifts, they are also dependent on a variety of guidelines to assist in the management of common orthopaedic presentations to the Emergency Department. The main issue is that site-specific guidance is not readily accessible on a single platform. Method: Smartphone and web-based applications were designed summarising the initial management for such conditions for the SHO on-call to use as a quick reference tool. The efficacy of this was evaluated with questionnaires specific to the rating of the application and by two closed loop audits of BOAST standards for the management of distal radius and ankle fractures. Results: Pre-app implementation questionnaire ratings revealed a mediocre confidence levels and high stress during an on-call shift. Post-app implementation questionnaires demonstrated the app was useful. Future use was recommended use for new SHOs. All responders felt that this would improve stress levels on call. Closed-loop audits for BOAST guidelines for ankle and distal radius fracture management were completed. Improvements were evident for obtaining appropriate radiographs ankle fractures (50.0% vs 77.8%) and positions of manipulated distal radius fractures (80% vs 100%). Conclusions: This application proved a useful reference tool for junior staff to aid and initiate the management of common orthopaedic presentations to the emergency department. This tool could be used to improve confidence and ensure timely management of patients from the take.